Coronectomía en terceros molares mandibulares como prevención para la lesión del nervio alveolar inferior: revisión bibliográfica - Sigcho Gonzalez, Rosemary Jessenia (2024)
The study focuses on coronectomy as a preventative measure to reduce inferior alveolar nerve (IAN) injury during mandibular third molar extraction. It is noted that if these molars do not erupt properly, they can lead to a number of complications. Coronectomy involves the removal of the tooth crown only, leaving the root in situ to reduce damage to the IAN. Therefore, the aim of this study is to perform a comprehensive review of the literature to know the results and complications of coronectomy and whether it is an appropriate procedure. A total of 30 scientific articles are included in the study, covering clinical case studies, reviews and case follow-ups, all of which met the pre-defined inclusion criteria and are sourced from various databases such as Google Scholar, PubMed, and ScienceDirect. Spreadsheets for data analysis are used in the Microsoft Excel programme, with the objective to achieve the outlined research objectives. As a result, it is determined that temporary paresthesia is the most common complication in 80% of cases (46.7%), followed by permanent paresthesia (33.3%) and other neurosensory lesions (20%). The incidence of complications varies depending on the position and difficulty of the case, with a greater prevalence observed in positions C, Class II according to Pell and Gregory, and the mesioangular position according to Winter. Regarding coronectomy, complications are observed in 37% of cases, with the most common being infection (21.62%), root migration (18.92%), postoperative paresthesia, and alveolitis (10.81%). Data analysis shows that coronectomy has a lower rate of IAN injury (15.19%) compared to total extraction (84.81%). It is concluded that coronectomy is a safe and effective technique to reduce the risk of inferior alveolar nerve (IAN) injury in patients with third molars in close proximity to the root complex